Removal Of Solids, Total Coliform, E.Coli, Uv254, Colour And Turbidity Using Zeolite Filter In Riverbank Filtration - Wahab, Muhammad Fikri Abd (Universiti Sains Malaysia, 2017)
Massive industrial development in recent years, and an increase in urbanization have caused severe water pollution problem especially to water supply source in Malaysia. Since many water bodies in Malaysia are heavily polluted, riverbank filtration (RBF) which uses natural attenuation process could be a possible low cost pretreatment option. However, the effectiveness of the RBF treatment were depends on the physical characteristics of the river water and the type of filter media used. Therefore, zeolite which is an adsorbent has the potential to modify the RBF system due to its ion-exchange and straining capabilities. In this study, the physical and chemical characteristics of zeolite were first determined by using Scanning Electron Microscopy (SEM) and X-Ray Fluorescence (XRF) method. Next, the zeolite was tested as a filter to remove particles, total coliform, E. Coli, total dissolved solids (TDS), suspended solids (SS), UV254, colour and turbidity. Zeolite with particle size 1.18 mm - 2 mm was used as porous media in the filter column as simulation to the RBF system. River water from Sungai Kerian, Lubok Buntar was characterized before conducted the column study. Based on the SEM results, the zeolite used were made from combination of micron-size crystal along with small size of pores. The presence of particles which less than 0.5 μm was found on the surface of zeolite after filtration. Next, the XRF results showed that the main components of the zeolite are SiO2 (79%) and Al2O3 (13%) that represents its Clinoptilolite group. The results from the column study showed that the removal of particles and total dissolved solids (TDS) using zeolite were not able to be determined due to the leaching effects of zeolite into the water. Besides that, the removal of total coliform and E. Coli were almost 100% of removal and no breakthrough occurred throughout the experiment. For suspended solids (SS) and turbidity, the removal were 80% - 85% and also no breakthrough occurred throughout the experiment. However, the removal of UV254 and colour achieved maximum value for the first three days of filtration with 60% - 73% for UV254 and 75% - 87% of removal for colour and almost achieved breakthrough at the end of experiment. Zeolite which is alkaline had also caused the increase of pH of the treated water.